Why Did the Extreme Drought in the Yangtze River Basin in 2022 Break the 2019 Record? - Linwei Jiang; Wenhao Gao; Kexu Zhu; Jianqiu Zheng; Baohua Ren (Earth and Space Science)
Abstract This study employs a multi‐faceted approach combining meteorological (Standardized Precipitation‐Evapotranspiration Index (SPEI)), agricultural (Soil Moisture (SM) percentiles), and land‐atmosphere moisture balance principles to comparatively analyze two unprecedented extreme drought events in the traditionally humid Yangtze River Basin during the summer to autumn of 2019 and 2022. The results reveal that, although both droughts persisted for roughly 2 months, the 2022 event exhibited a more abrupt onset and greater intensity. Soil moisture levels in 2022 plummeted below 5%, surpassing the severity of the 2019 drought and marking it as the most severe regional drought on record. The daily SPEI calculations effectively tracked the progression of both droughts, demonstrating a strong correlation with fluctuations in SM. The 2019 drought followed a traditional pattern, developing gradually and primarily driven by prolonged precipitation deficits. In contrast, the 2022 drought was characterized as a flash drought, triggered by extreme heatwaves under a pre‐existing wetter condition, which induced a positive feedback loop among high temperatures, increased evaporation, and reduced SM. The rapid reduction in SM further decreased soil heat capacity, exacerbating daytime temperature. Moisture budget analysis shows that, in 2019, the persistent moisture deficiency stemmed from wind divergence obstructing the moisture supply, leading to prolonged periods of local dryness and a gradual buildup of the drought. In 2022, extreme heat‐induced elevated Evapotranspiration (ET) further exacerbated SM loss, intensifying the drought and causing it to develop rapidly. Moreover, both droughts were significantly influenced by the position and strength of the Western Pacific subtropical high (WPSH).